Moral Reasoning in Bodybuilding - Agnė Kelaitytė; Diana Karanauskienė (Lithuanian Sports University, 2020)
Background. The aim of the research was to disclose the process of moral reasoning in bodybuilding: to reveal the features of bodybuilding sport (athletes' goals, benefits of the sport and its costs), to find out the circumstances which can affect athletes' moral decisions, to evaluate bodybuilding athletes' moral reasoning strategies, and to reveal athletes' most important moral decisions. Methods. The study employed qualitative research which involved eight bodybuilding athletes. The respondents were selected using the theoretical purposeful convenience sampling strategy. A semi-structured interview method was used to collect information. Results. Athletes' goals in bodybuilding can be sports related (getting to know the sport, athletic achievements) or personal (moral and psychological toughness, personal improvement, self-realization, material benefits).  Bodybuilders benefit from the sport in physical (health and appearance improvement) and social (gained experience, self-realization) ways. The price of this sport is athletes' hard work, large amounts of money, sacrificed personal life and deterioration of psychological and physical health. Moral reasoning can be influenced by positive circumstances (bodybuilding philosophy, internal beliefs, fighting against cheating, team spirit) and negative (ingrained misdemeanours in sport, corruption, flawed rating system, possibility to avoid responsibility, big price of winning, psychological pressure, inadequate goals). Athletes most often use rational moral reasoning strategies (regarding their beliefs, solution seeking, situational decisions, self-mobilization, setting options, relying on experience). Athletes more often make positive moral decisions (changing the trainer, following the rules, resisting pressure, moral behaviour) than negative (adapting to the situation, acting like the others, winning at any cost). Conclusions. Bodybuilders most often aim for personal goals. Bodybuilding provides its athletes with physical and social benefits. The price of this sport is bodybuilders' hard work, large sums of money, sacrifice of personal life and health. Certain circumstances might influence athletes to make positive moral decisions while others might influence negative decisions. Bodybuilding athletes use two different moral reasoning strategies: rational or irrational. Bodybuilders' more often make positive moral decisions, but negative decisions occur as well.  Keywords: morality, moral reasoning, bodybuilding.